HF, DFT Studies and NBO Analysis of Phosphazenes and Its-Na+ Complex - Lamine Abdelatif, Mohamed; Belmiloud, Yamina; Brahimi, Mziane (Asian Journal of Chemistry, 2010)
In this work, we study simple phosphazenes models, such as H3PNX and F3PNX (X = H, F and OH). Several bonding theories have been presented to explain the observed structural properties in polyphosphazenes of which the dπ-pπ bonding model is most widely adopted. But there is no report on the degree of participation of the 3d and 2p orbital of phosphorus and nitrogen atom respectively, at the dπ-pπ bond, type of natural orbital hybrid (NOH) to form this π-bond in the phosphazenes compounds and in the phosphazene-Na+ complex. The aim of this work is to attempt to investigate these aspects by means of HF and DFT studies of electronics, molecular structures and natural bond orbital (NBO) analysis.